TECTONO-SEDIMENTARY EVOLUTION AND RATES OF TECTONIC UPLIFT OF THE SFAKIA COASTAL ZONE, SOUTHWESTERN CRETE - Skourtsos, E.; Pope, R.; Triantaphyllou, M. V. (Bulletin of the Geological Society of Greece, 2007)
Sfakia lies within a narrow coastal zone at the southwestern foothills of the Lefka Ori Mt. Here a segment of the South Cretan margin is preserved onshore, a structure that represents a neotectonic structure with continuous activity since the Upper Miocene. This segment is characterized by a steep, E-W striking and south facing morphological escarpment that constitutes numerous E-W and ESE-WNW striking normal faults. Since the Late Miocene, marine sequences of Tortonian, Early Pliocene and Lower Pleistocene age were deposited along the coastal zone. Since the Middle Pleistocene multiple, coalescent alluvial fans covered both the alpine basement and the marine sediments. Fault-kinematic- and stratigraphie data combined with recently published palaeobathymetry reconstructions allow us to make relable estimates of both the uplift rates of fault blocks in the study area and the period that the faults that demarcate them were active. The results show that the study area is experiencing uplift already since the Middle Pliocene and that the uplift rates of the mountainous parts are higher than those of the coastal zone. The general uplift of the coastal zone seems to be controlled by offshore normal faults, south of Sfakia